PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN PENDEKATAN DISCOVERY LEARNING PADA MATERI BARISAN DAN DERET KELAS X REKAYASA PERANGKAT LUNAK - Eko Hendi Prabowo; Puji Nurfauziah; Masta Hutajulu (IKIP Siliwangi, 2022)
Series and sequences one of the most important sub-topics in mathematics since students frequently make mistakes or forget formulae when solving problems, which has an impact on learning results. This study tries to explain how a discovery learning strategy at the vocational high school level improved student learning results in class X. This study is an example of classroom action research. The class X pupils at one of the Cimahi Vocational High Schools served as the study's subjects to determine whether the instructor has a direct impact on the learning process. With the Discovery learning strategy, this project seeks to enhance students mathematics learning results. According to the analysis of learning outcomes and completeness scores, cycle I students mathematics learning outcomes demonstrated a moderate level of material mastery with only 33% of students completing them, whereas cycle II students' mathematics learning outcomes demonstrated a high level of material mastery with 75% of students completing them. The class X SMK's mathematics learning outcomes can be enhanced by the discovery learning technique.